Analytical Procedures for Determination of Paroxetine in Pharmaceutical Formulations - FELICE CHORAGUDI, SHECHINAH; SETTALURI, V.S.; KAYASTHA, SHILVA; DEVATHU, PRATHYUSHA; KROTHAPALLI, UJJWALA (Asian Journal of Chemistry, 2010)
Sophisticated analytical methods viz., HPLC and HPTLC which are employed for analysis of drugs are relatively expensive for the utilization by small scale industries. Hence need for simple analytical methods arises, which are suggested in the proposed methods for routine determination of paroxetine in pharmaceutical formulations and bulk dosage forms.These methods are based on the formation of coloured species on binding of paroxetine with potassium ferricyanide and ferric chloride reagent to produce a greenish yellow coloured chromogen (lmax at 710) for method A and sodium nitrite and conc. HCl to produce a pale yellow coloured chromogen (lmax at 490) for method B. Results of analysis were validated statistically and by recovery studies. Based on the principle of absorption visible spectrophotmetry and the results obtained the methods could be treated as simple, sensitive and reproducible for the determination of paroxetine in pharmaceutical formulations.